My boy will die of sorrow : a memoir of immigration from the front lines - Olivares, Efrén C. (Hachette Books, 2022)
"The principles that ostensibly bind America together-mutual respect for the Constitution and its institutions, and reciprocal adherence to principles such as freedom, the rule of law, due process, and equality under the law-fall apart at our borders. As those values dissolve at our country's frontiers, they allow for otherwise impermissible cruelty towards those who are considered outsiders. My Boy Will Die of Sorrow follows several specific characters - desperate parents who have been separated from their children and are being treated as criminals. By sharing these gripping family separation stories alongside his own story of emigrating to the U.S. at thirteen, Olivares gives voice to all immigrants who have been punished and silenced for seeking safety and opportunity. Olivares reflects on the immigrant experience, then and now, on what separations do to families, and how the act of separation itself adds another layer to the immigrant identity. In the telling of these stories, he explores how our concern for fellow human beings who live at the margins of our society-at the border, literally and figuratively-is affected by how we view ourselves in relation both to our fellow citizens and to immigrants. His personal journey also serves as a counter-narrative to claims that a majority of immigrants are criminals who do not contribute to American society and should be kept out. And by examining his personal story and the stories of the families he represents side by side, he hopes to meaningfully engage readers with their assumptions about what nationhood means in America and be challenged to question their own empathy and compassion. He paints a portrait of an America that is simultaneously-a nation of immigrants but also a nation against immigrants"--